Study of Magnesium Formulations on Intestinal Cells to Influence Myometrium Cell Relaxation - Francesca Uberti (Nutrients, 2020)
Background: Magnesium is involved in a wide variety of physiological processes including direct relaxation of smooth muscle. A magnesium imbalance can be considered the primary cause or consequence of many pathophysiological conditions. The smooth muscle tissue of the uterus, i.e., the myometrium, undergoes numerous physiological changes during life, fundamental for uterine activities, and it receives proven benefits from magnesium supplementation. However, magnesium supplements have poor absorption and bioavailability. Furthermore, no data are available on the direct interaction between intestinal absorption of magnesium and relaxation of the myometrium. Methods: Permeability in human intestinal cells (Caco-2 cells) and direct effects on myometrial cells (PHM1-41 cells) of two different forms of magnesium, i.e., sucrosomial and bisglycinate, were studied in order to verify the magnesium capacity of modulate contractility. Cell viability, reactive oxygen species (ROS) and nitric oxide (NO) production, magnesium concentration, contractility, and pathways involved were analyzed. Results: Data showed a better influence of buffered chelate bisglycinate on intestinal permeability and myometrial relaxation over time with a maximum effect at 3 h and greater availability compared to the sucrosomial form. Conclusions: Magnesium-buffered bisglycinate chelate showed better intestinal absorption and myometrial contraction, indicating a better chance of effectiveness in human applications.